1987
DOI: 10.1017/s0317167100026688
|View full text |Cite
|
Sign up to set email alerts
|

Hand Wasting Due to Mid-Cervical Spinal Cord Compression

Abstract: Three patients presented with hand wasting and weakness secondary to mid-cervical spinal cord compression. This was due to cervical spondylosis in two patients and a meningioma in one case. This phenomenon is probably similar to that seen with foramen magnum lesions and may be due to spinal cord ischemia distal to the compression, secondary to venous stasis. RESUME: Atrophie de la main due a une compression medullaire localisee a la region cervicale moyenne. Trois patients ont consulte pour de l'atrophie et de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The site of conduction block identified by the A-SCEP and the D-SCEP, whether the two studies revealed conduction block at the same single level (78 out of 83 patients) or at two separate levels (5 out of 83 patients), corresponded to the intervertebral level of sufficient degree of cord compression with MRI evidence of either the smallest anteroposterior diameter and cross-sectional area of the cord (for 81% of 88 conduction blocks) or the second smallest anteroposterior diameter and crosssectional area of the cord (for 19% of 88 conduction blocks). This finding indicates the functional importance of direct mechanical pressure on the white matter rather than vascular factors involving the gray matter remote from the site of compression, thus causing false localizing signs [12]. Measuring the absolute values of anteroposterior diameter and cross-sectional area of the cord has a limitation in estimating the degree of cord compression, because the spinal cord varies in size depending on the level; the anteroposterior diameter normally decreases, and the One-way ANOVA followed by Tukey HSD test is used for statistical analysis "0" represents the site of conduction block, with the other levels numbered in order of increasing distance from the "0" level, assigning a minus sign caudally Anteroposterior diameter of the cord was measured on midsagittal T1weighted MRI…”
Section: Discussionmentioning
confidence: 93%
“…The site of conduction block identified by the A-SCEP and the D-SCEP, whether the two studies revealed conduction block at the same single level (78 out of 83 patients) or at two separate levels (5 out of 83 patients), corresponded to the intervertebral level of sufficient degree of cord compression with MRI evidence of either the smallest anteroposterior diameter and cross-sectional area of the cord (for 81% of 88 conduction blocks) or the second smallest anteroposterior diameter and crosssectional area of the cord (for 19% of 88 conduction blocks). This finding indicates the functional importance of direct mechanical pressure on the white matter rather than vascular factors involving the gray matter remote from the site of compression, thus causing false localizing signs [12]. Measuring the absolute values of anteroposterior diameter and cross-sectional area of the cord has a limitation in estimating the degree of cord compression, because the spinal cord varies in size depending on the level; the anteroposterior diameter normally decreases, and the One-way ANOVA followed by Tukey HSD test is used for statistical analysis "0" represents the site of conduction block, with the other levels numbered in order of increasing distance from the "0" level, assigning a minus sign caudally Anteroposterior diameter of the cord was measured on midsagittal T1weighted MRI…”
Section: Discussionmentioning
confidence: 93%